Study of load-deformation distribution in normal and implanted lumbar motion segment - Chia, Emileen Siok Chen. (2008)
There is little information about the influence of bone graft elasticity on the mechanical behavior of a L2-L4 motion segment implanted with both interbody implant (spacer) and posterior instrumentation (pedicle screws and rods). IN this study, intersegmental motion and stress level induced at spacer and bone graft were calculated using a three-dimensional nonlinear finite element mode.